Quality and quantity of Aspergillus niger DNA isolation using filter-based kit and cooling method - Renatasya Silviana Herningtyas; Qurrohman, Muhammad Taufiq (International Journal of Health Science and Technology, 2024)
Polymerase Chain Reaction (PCR) is an important technique to improve sensitivity in the detection of fungal infections, such as those caused by Aspergillus niger. The availability of pure DNA and DNA isolation techniques are important factors in implementing PCR. This study aims to compare the quality and quantity of DNA isolation of Aspergillus niger using the Filter Based Kit method and cooling. The experimental research design was used with a qualitative test of DNA isolate using Agarose Gel Electrophoresis (1.5%) and a quantitative DNA test using a UV-Vis Spectrophotometer (wavelengths of 260 nm and 280 nm). Data analysis compared the qualitative and quantitative results of DNA isolates from both methods. The results showed the presence of DNA bands in both isolation methods, with thicker bands in the Filter Based Kit method. The average concentration of DNA after isolation using the Filter Based Kit (6,478 ng/μl) was higher than that of the cooling method (5,994 ng/μl). The purity of DNA was also higher in the filter-based kit (1.7) than in the cooling method (1.1). The Filter Based Kit method contains chemical components that support the successful isolation of DNA. It can be concluded that the filter-based kit method produces Aspergillus niger DNA isolate with better quality and quantity than the cooling method. The implication of these findings is that the Filter Based Kit could be a better option for the isolation of Aspergillus niger DNA in laboratory applications.